Drug Utilization Evaluation Study in a Tertiary Care Hospital - Ubhe, Tejaswi; Dokh, Rutuja; Bhujbal, Shweta; Joshi, Nupuri; Tuse, Trupti; Pisure, Manoj (Indian Journal of Pharmacy Practice)
Background: Not administering medicines as per the prescribed guidelines can result in subtherapeutic or toxic effects by taking dose too early or too late. It could have a negative impact on the patient or resulting in an additional financial burden. Materials and Methods: A Prospective observational study was carried out in the inpatients of tertiary care hospital. Total 400 patients and 1050 medication administrations were studied over a period of 6 month for timely medication administration. The error was assessed using ISMP (Institute for Safe Medication Practices) guidelines. Results: The numbers of females were 146 and 254 males forming total 400 patients. Total 1050 medication administrations were evaluated, 681time critical and 369 medication administrations were non-time critical. Before awareness program, out of 515 medication administrations 263 were on time (51.07%), while 252 administrations deviated from the scheduled time (48.93%). After awareness program, out of 535 medication administrations, 413 were on time (77.20%), while 122 administrations deviated from the scheduled time (22.80%). Difference in scheduled time and administration time for time critical medication administrations, was reduced by 22 min 33 sec±11 min 58 sec after the awareness program, while for non-time critical medication administrations the time was reduced by 12 min 14 sec±9 min 87 sec, after the awareness program. Conclusion: Timely administration of medications is crucial to prevent harm and therapeutic failure. Educating nursing staff can help prevent errors improve patient care.
Keywords: Heavy patient load; ISMP guidelines; Time critical medications; Timely medication administration